1991
DOI: 10.1123/apaq.8.2.107
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Field Based Cardiovascular Fitness Running Tests for Individuals with Mental Retardation

Abstract: The primary purpose of this investigation was to determine the reliability of cardiovascular running tests for individuals with mild and moderate mental retardation. A secondary purpose was to determine whether cardiovascular running tests had some degree of validity in that running times for these tests tended to be in excess of 6 minutes. Data for eight groups were analyzed. Times for the distance runs ranged from 51 to 914 seconds while reliability ranged from .25 to .94, depending on the group. Based on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

1995
1995
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
4
0
1
Order By: Relevance
“…While the 1-mile (1.6 km) run is most commonly used for children over the age of 10 years, motivational factors may elicit poor results in a test of such long duration for children with MR (Rimmer, 1994). Distances from 600 yards (548.6 m; Fernhall et al, 1998;r = .96-.98) to 880 yards (804.6 m; Pizarro, 1990; r = .8-.9) have been used to measure cardiovascular fitness reliably in adolescents with MR. Fernhall and colleagues (1998) found the 600-yard (548.6 m) run explained 74% of the variance of VO 2 peak in adolescents with MR. Baumgartner and Horvat (1991) suggested the 880-yard (804.6 m) run with adolescents with MR appeared to be a valid measure of aerobic capacity, based on construct validity. Downloaded by [University of Illinois Chicago] at 14:59 13 October 2014 Foley, Harvey, Chun, and Kim Abdominal strength was determined by having participants complete as many sit ups as possible in 1 min.…”
Section: Data Collectionmentioning
confidence: 98%
“…While the 1-mile (1.6 km) run is most commonly used for children over the age of 10 years, motivational factors may elicit poor results in a test of such long duration for children with MR (Rimmer, 1994). Distances from 600 yards (548.6 m; Fernhall et al, 1998;r = .96-.98) to 880 yards (804.6 m; Pizarro, 1990; r = .8-.9) have been used to measure cardiovascular fitness reliably in adolescents with MR. Fernhall and colleagues (1998) found the 600-yard (548.6 m) run explained 74% of the variance of VO 2 peak in adolescents with MR. Baumgartner and Horvat (1991) suggested the 880-yard (804.6 m) run with adolescents with MR appeared to be a valid measure of aerobic capacity, based on construct validity. Downloaded by [University of Illinois Chicago] at 14:59 13 October 2014 Foley, Harvey, Chun, and Kim Abdominal strength was determined by having participants complete as many sit ups as possible in 1 min.…”
Section: Data Collectionmentioning
confidence: 98%
“…In the current study, the standard deviations of the individuals with MMR are generally greater than those without. Largely dispersed scores usually result in higher correlation coefficients (Baumgartner & Horvat, 1991;Bland & Altman, 1990;Sale, 1991;Watson, 1995) The use of 95% CIS thus offers a more accurate and applicable estimate of reliability. Independent student t test group comparisons (see Table 2) indicated that male adolescents with MMR scored significantly poorer ( I .005) on all variables except for height and weight.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the ICC for the sit-and-reach test for male adolescents with MMR is R = .97, the corresponding 95% CI is 4.9 cm, and the percentage error of the mean is 47.6%. This lack of agreement may be explained by the effect that the dispersion of scores has on correlations (Baumgartner & Horvat, 1991;Bland & Altman, 1990;Sale, 1990;Watson, 1995). Thus, investigators should carefully consider which analysis method is used to establish reliability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eπιπλέον άλλοι ερευνητές ανέφεραν ότι το τρέξιµο 6 λεπτών µπορεί να χρησιµοποιηθεί για την εκτίµηση της αερόβιας ικανότητας σε άτοµα µε Ν.Κ. (Baumgartner & Horvat, 1991, Disch, Frankiewicz & Jackson, 1975.…”
Section: β) αερόβια ικανότηταunclassified